Several Factors Affecting Taxpayer Compliance: Service Quality as a Moderating Variable - David Chandela; Robinson Robinson; Eddy Suranta (Goodwood Publishing, 2026)
Purpose: This study examines the influence of tax knowledge, tax awareness, moral obligation, trust in government, and service system simplicity on taxpayer compliance, with service quality as a moderating variable, drawing on the Theory of Planned Behavior (TPB) and the Slippery Slope Framework (SSF). Research Methodology: Data were collected from 117 restaurant taxpayers in Rejang Lebong Regency, Indonesia, through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. Results: Tax knowledge, tax awareness, trust in the government, and service system simplicity had a positive and significant effect on taxpayer compliance, whereas moral obligation had a negative and insignificant effect. Service quality does not significantly moderate the tax awareness-compliance relationship, but it strengthens the moral obligation-compliance relationship. Conclusions: The results support the TPB and SSF, emphasizing that voluntary compliance is primarily driven by trust and awareness, whereas moral factors become effective only in a high-quality service environment. Limitations: This study used a cross-sectional design and was limited to restaurant taxpayers, which may restrict the generalizability of the results. Contributions: This study integrates behavioral and institutional perspectives on tax compliance at the local government level and offers practical implications for improving service quality and voluntary compliance in developing areas.